IDENTIFICATION OF RESTORERS AND MAINTAINERS FOR THE DEVELOPMENT OF RICE HYBRIDS - M. Akhter; M. A. Zahid; M. Sabar; M. Ahamd (Journal of Animal and Plant Sciences, 2008)
Two hundred thirty nine (239) rice genotypes were evaluated for their status in hybrid rice gene pool during 2005 and 2006. From these 239 test crosses twelve (12) restorers and 16 maintainers (8 Basmati and 8 non basmati lines) were identified for use in hybrid rice breeding programs. Four basmati and eight coarse lines were identified as restorers from the tested genotypes. Most of the genotypes were found partial restorer and partial maintainer. In addition, eight best heterotic combinations were also identified. Six heterotic hybrid combinations had more than 80% spikelet fertility. Plant height of all the hybrids was less except IR 70372 / Bas 370 and IR 58025A / PK 1498-6-2-4 than check variety basmati 385. Filled grains per panicle of the hybrids ranged from 101.2 to 145.2 as compared to the check variety (84.6).
Keywords: Genotypes; Basmati; Heterotic; Grains